Permasalahan Teori Peluang dan Statistika dan Alternatif Solusi di Kelas VI Sekolah Dasar - Ermawasari, Ermawasari; Fauzan, Ahmad; Zainil, Melva (Innovative: Journal Of Social Science Research, 2024)
This article discusses the problems faced in learning opportunity theory and statistics in grade VI of elementary school and proposes alternative solutions to overcome these obstacles. The main problems identified include students' lack of understanding of the concept of opportunity and statistics, the limitations of interactive learning media, and teaching methods that are less relevant to students' needs and life contexts. As an alternative solution, this article offers a more contextual approach, such as the use of concrete learning media, the use of technology in learning, and the application of project-based learning methods that are able to relate theoretical concepts to real situations. With this strategy, it is hoped that students can better understand the material of opportunity and statistics, increase learning motivation, and apply knowledge in daily life.